INFORMATION NOISE AND MARKETING TOOLS TO OVERCOME IT (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the modern conditions of the formation of the digital economy and the intensive growth of the volume of information to be processed by analysts, fundamentally new requirements are being formed for consumers and businesses. At the same time, data processing tools do not always provide adequate analytical information regarding changes occurring both in the global and local markets. The reason for this is information noise, which is an excessive flow of data that complicates the perception of important messages and affects the effectiveness of marketing strategies. All this requires the formation of a systematic approach to managing information flows and optimizing communications between the enterprise and the target audience.The purpose of the article. The purpose of the study is to analyze information noise as a barrier to the effective perception of marketing communications, as well as to identify tools and strategies that allow minimizing its impact on consumers and increasing the effectiveness of marketing activities.Methods. The research is based on the use of an interdisciplinary approach, which includes content analysis, abstract modeling methods for studying consumer perception of information, as well as empirical methods for studying the effectiveness of modern marketing technologies, based on the analysis of approaches to managing specialized marketing tools for interacting with consumers.Results. The article considers the conceptual aspects of information noise and its functional impact on consumer behavior. The effectiveness of using various marketing tools based on the automation of business processes, the use of communication platforms and data for analyzing consumer behavior is analyzed, which results in increasing the efficiency of communications and reducing noise effects. Key strategies for combating information noise are identified, which contribute to strengthening the communication interaction of the enterprise in the context of dynamic changes in market conditions. The need for implementing innovative approaches to developing advertising campaigns that take into account the specifics of modern media channels and consumer behavioral models is proven.Conclusions. It has been proven that minimizing information noise is an important factor in ensuring the long-term effectiveness of a company's marketing communications. It has been determined that the use of modern data analysis tools, process automation, and an individual approach to the consumer allows a company to increase the level of trust and loyalty from customers, which results in an increase in sales and profitability of the business entity.
Keywords: information noise, marketing, content personalization, innovative marketing strategies, market communications.